PSYCHOTHERAPY IN GEORGIA: PAST, PRESENT AND FUTURE - Revaz Korinteli (European Scientific Journal, ESJ, 2014)
The presented article describes the social, political and economic conditions influencing psychotherapy in post-Soviet Georgia. The author describes the so-called post-Soviet phenomena and defines its following aspects: 1. Master-Slave Relationship between the State and the People ; 2. Nostalgia for the Past and Idealisation of the Soviet Times; 3. Identity Crises; 4. Materialistic World View ; 5. Societal Traumas; 6. Political-economic Conditions. The paper describes the correlation between the post-Soviet phenomena and the challenges of practising psychodynamic psychotherapy.